Social media addiction and borderline personality disorder: a survey study - Collins, Madison; Grant, Jon E. (Frontiers in Psychiatry, 2025)
Background and aimsBorderline personality disorder (BPD) is a serious and difficult to treat psychiatric condition characterized by affective and interpersonal instability, impulsivity, and self-image disturbances. Although the relationship between BPD and substance use disorders has been well-established, there has been considerably less research regarding behavioral addictions in this population. The purpose of this study is to determine the prevalence of social media addiction (SMA) among individuals with BPD and to explore whether it is related to aspects of disorder symptomology.Methods300 adults completed an online survey via Prolific. Individuals completed the McLean Screening Instrument for BPD (MSI-BPD), along with the Bergen Social Media Addiction Scale (BSMAS). Additionally, all participants reported how often they use social media for the following reasons: distraction from interpersonal problems, reassurance seeking, self-confidence issues, and anger/revenge.ResultsOf the 289 subjects that completed all measures, 38 (13.1%) screened positive for BPD. Individuals screening positive for BPD were more likely to meet criteria for SMA than controls, and they were more likely to report using social media for interpersonal distraction, reassurance seeking, self-confidence issues, and anger/revenge seeking than controls. Among individuals with BPD, SMA was positively associated with the frequency of each of these behaviors, except for anger/revenge seeking.Discussion and conclusionThe results of this study demonstrate that SMA is common among the BPD population and may be related to aspects of disorder symptomology. Whether SMA worsens BPD symptoms or whether addressing SMA could lead to improvements in the BPD remains to be seen and is an important area for future research.